Tourism in the Soviet Carpathians: Accommodation facilities for qualified tourism in the Eastern Carpathians (Lviv and Ivano-Frankivsk oblast) in the 1970s and 1980s - Quirini-Popławski, Łukasz; Kudła, Nazar; Rytynski, Michajło (Turyzm/Tourism, 2019)
The research issue is to describe the tourist accommodation used for specialised tourism, including its types, distribution and scale, in the northern part of the Eastern Carpathians in the former Ukrainian Soviet Socialist Republic. The authors focused on the 1970s and 1980s which were the ‘golden age’ in the development of tourism in the Soviet Union. As a result of the analysis, 51 accommodation facilities were identified offering nearly 7,300 beds in the mid-1980s. It was the time when the development of that area reached its peak.